PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM LUMBUNG GIZI SUMBER ASRI SEBAGAI PEMBENTUKAN KETAHANAN PANGAN DI DESA SUMBER ASRI - Ayu Novitrie; Alif Prasetya Senja; Alzikra Arfi; Dian Rachmanissa Putri; Shabrina Putri Johani; Annisa Juni Arni; Putri Thalia Fortuna Sianipar; Tazkia Ramadhani; Salsabilla Oktarina; Dwita Febriana; Najwa Shakinah Rachmania Asri; Ratri Pramu Ditha (PARIPALAKA SRIWIJAYA, 2025)
The Sumber Asri Nutrition Barn Program was implemented as a community empowerment initiative aimed at building food security based on local potential in Sumber Asri Village, Lubai Ulu District, Muara Enim Regency. The lack of access to nutritious food and low consumption of vegetables and medicinal plants prompted the execution of this program. The activities were conducted through participatory education, interactive counseling, and indirect demonstrations involving 30 participants consisting of housewives and heads of families. Educational materials were delivered visually and interactively, followed by a demonstration video on making fertilizer from food waste, and direct planting of various crops such as spinach, water spinach, mustard greens, lemongrass, galangal, turmeric, and basil. The program showed success through active community participation in discussions, understanding of food security principles, and the ability to plant independently. Collaboration with village officials further supported the program’s sustainability by initiating the use of home yards as independent food sources. The findings indicate that a community-based approach through education and practical implementation can raise public awareness in managing food sustainably. This success serves as a tangible example of the synergy between education, environment, and village policy in realizing empowered and independent food security